Charlie's angels [videorecording (DVD)] - Banks, Elizabeth, 1974-; Banks, Elizabeth, 1974-; Banks, Elizabeth, 1974-; Banks, Elizabeth, 1974-; Stewart, Kristen, 1990-; Scott, Naomi, 1993-; Balinska, Ella, 1996- (Sony Pictures Home Entertainment, 2020)
Working for the mysterious Charles Townsend, three highly trained women investigate criminal activity and report to multiple Bosleys.